Combining locoregional CAR-T cells, autologous + allogeneic tumor lysate vaccination and levamisole in treatment of glioblastoma. (2nd November 2022) - Altinoz, Meric A.; Ozpinar, Alp; Hacker, Emily; Ozpinar, Aysel
Abstract: Glioblastoma multiforme (GBM) is an aggressive brain malignancy and harbors a microenvironment limiting immune cells activity. CAR-T cells are being tested in the treatment of cancers and there exist reports which demonstrate dramatic regression of multicentric GBMs following intrathecal treatment with CAR-T cells. In this article, a triple approach for immune treatment of GBM is proposed. First, GBM tumor specimens for each patient will be saved and cultured to obtain tumor lysates. Then, levamisole will be applied, which possesses immunostimulating, anti-glycolytic, and anti-angiogenic features. Following priming the immune system, GBM patients will be injected with lysates of their own tumor cells plus lysates from a GBM cell line, U251. After 3 months of this treatment, CAR-T cells (transduced with IL13Rα2-CAR) will be applied via intratumoral approach. As such, genetically-modified and native immunocytes may 'meet' in the vicinity of deeply-invading tumor cells and demonstrate greater efficacy via cell-cell interactions. By this, a self-propagating cyclic process – a cancer-immunity cycle – may be initiated to eradicate cancer cells.